α2–6-Neosialidase: A sialyltransferase mutant as a sialyl link-age-specific sialidase - McArthur, John B. (ACS Chem Biol, 2018)
The lack of α2–6-linkage specific sialidases limits the structural and functional studies of sialic acid-containing molecules. Photobacterium damselae α2–6-sialyltransferase (Pd2,6ST) was shown previously to have α2–6-specific, but weak, sialidase activity. Here we develop a high-throughput blue-white colony screening method to identify Pd2,6ST mutants with improved α2–6-sialidase activity from mutant libraries generated by sequential saturation mutagenesis. A triple mutant (Pd2,6ST S232L/T356S/W361F) has been identified with 100-fold improved activity, high α2–6-sialyl linkage selectivity, and ability in cleaving two common sialic acid forms N-acetylneuraminic acid (Neu5Ac) and N-glycolylneuraminic acid (Neu5Gc). It is a valuable tool for sialoglycan structural analysis and functional characterization. The sequential saturation mutagenesis and screening strategy developed here can be explored to evolve other linkage-specific neoglycosidases from the corresponding glycosyltransferases.